(untitled) (Indian Journal of Veterinary Pathology, 2025)
This study investigates the prevalence and characteristics of ovarian pathologies in sheep, focusing on reproductive efficiency’s impact on productivity. A total of 212 ovaries from 106 sheep were examined using gross, cytological and histopathological techniques. Of these, 62.26% were normal, while 37.73% exhibited pathological abnormalities, comprising 18.39% neoplastic and 19.34% non-neoplastic conditions. Granulosa cell tumors were the most common neoplastic condition (7.55%), followed by adenomas (4.72%) and hemangiosarcomas (1.89%). Histopathological analysis revealed distinct features, such as Call-Exner bodies in granulosa cell tumors and papillary projections in adenomas. Among the non-neoplastic conditions, follicular cysts were the most prevalent (6.13%), followed by folliculoids (3.77%) and embedded corpus luteum (2.36%). Microscopically, these lesions demonstrated consistent features, such as granulosa cell absence in follicular cysts and fibrous connective encapsulation in embedded corpus luteum. The study highlights significant variations in pathological prevalence between left and right ovaries, with the right ovary more commonly affected. These findings align with existing literature, supporting their diagnostic validity and emphasizing the impact of ovarian abnormalities on reproductive health. By identifying and characterizing these conditions, this research contributes to improved diagnostic accuracy and the development of strategies to enhance reproductive efficiency in small ruminants, ultimately supporting rural livelihoods and food security.